Physical activity and its association with quality of life in patients with osteoarthritis - de Figueiredo Neto, Esmeraldino Monteiro [UNESP]; Queluz, Thais Thomaz [UNESP]; Freire, Beatriz Funayama Alvarenga [UNESP] (My University, 2011)
Objective: To evaluate the quality of life and its association with daily physical activity in different contexts of life in osteoarthritis patients referred from Basic Health Care Units to a university-affiliated service. Methods: This is a cross-sectional, case series study in which physical activity was evaluated by the International Physical Activity Questionnaire (IPAQ), and quality of life was assessed by the Medical Outcomes Study 36 Short-Form Health Survey (SF-36), Western Ontario and McMaster Universities Index (WOMAC), and Australian/Canadian Osteoarthritis Hand Index (AUSCAN). To evaluate pain intensity, a Visual Analogue Scale (VAS) was also used. Results: One hundred patients (92 women and eight men; mean age 59.9 ± 9.4 years) were included. The most affected joints were the knees and hands. Ten patients had only a single joint affected, 69 patients had two, eight patients had three, and 13 patients had four joints affected. The IPAQ showed that 70 patients were active or very active, while 30 were insufficiently active or sedentary. Physical activity was positively associated with the SF-36 domains that assess physical health (physical functioning, physical role, pain, general health perceptions). There was an association between physical activity and quality of life assessed by WOMAC, and the more severe the pain, the worse the quality of life. Conclusion: In most patients in this population, the physical aspects of the quality of life are worse, but they maintain their daily physical activities. © 2011 Elsevier Editora Ltda. All rights reserved.
Keywords: Motor activity; Osteoarthritis; Quality of life